Nightwork - Roberts, Nora (New York St. Martin's Press, 2022)
"Harry Booth started stealing at nine to keep a roof over his ailing mother's head, slipping into luxurious, empty homes at night to find items he could trade for precious cash. When his mother finally succumbed to cancer, he left Chicago--but kept up his nightwork. Wandering from the Outer Banks to Savannah to New Orleans, he dons new identities and stays careful, observant, distant. He can't afford to attract attention--or get attached. Still, he can't help letting his guard down when he meets Miranda Emerson. But the powerful bond between them cannot last--because not all thieves follow Harry's code of honor. Some pay others to take risks so they can hoard more treasures. Some are driven by a desire to own people the way they own paintings and jewels. And after Harry takes a lucrative job commissioned by Carter LaPorte, LaPorte sees a tool he can use, and decides he wants to own Harry. The man is a predator more frightening than the alligators that haunt the bayou--and when he strongarms Harry into robbing a Baltimore museum, Harry abandons Miranda--cruelly, with no explanation--and disappears. But no matter what name he uses or where he goes, LaPorte casts a shadow over Harry's life. To truly free himself, he must face down his enemy once and for all. Only then can he hope to possess something more valuable than anything he has ever stolen."--
110520
Keywords: Honor -- Fiction; Thieves; Swindlers and swindling; Man-woman relationships; Stealing; Suspense fiction; Romance fiction; Thrillers (Fiction)